Socialism, Communism, and Concrete Marxism. Issue 4 (2nd October 2022) - Balasopoulos, Antonis; Boer, Roland
ABSTRACT: This dialogue begins with the question of "concrete Marxism, " which is at the foundations of "Socialism with Chinese Characteristics." The concrete is analysed in terms of Marx's dialectic between freedom and necessity, as also in Marx's early work on Epicurean materialism and in Engels's "Dialectics of Nature" and "Anti-Dühring." We include a discussion of Hegel's dialectic between the actual and the rational. Subsequently, we move to the relationship of socialist construction to the (non-socialist) past and a socialist future. We adduce examples from Marx's "The Eighteenth Brumaire of Louis Bonaparte, " as well as the Chinese concept of mingyun (destiny/future) and explore the implications of Lenin's critique of "left wing" impatience with the past. The issue here is the mistake of a "leftist" effort to make the leap—through sheer voluntary effort—into communism as an over-compensation for practical deficiencies and, on the other hand, the possibility for revolutionary socialism of appropriating and transforming the positive advances of bourgeois culture and civilisation. We conclude with some preliminary observations on the communist prospect, emphasising the concrete form of the dialectic of productive forces and relations of production and the reasons why this form highlights the importance of the former as a motive force.